Anti-inflammatory efficacy and skin irritation study of Cleome gynandra extract: an animal model and pre-clinical evaluation - Muhammad Aiman, H.I.; Koh, S.P.; Sew, Y.S.; Sanimah, S.; Chandradevan, M.; Muhammad Nazrul, H.; Armania, N. (Rynnye Lyan Resources, 2024)
Cleome gynandra, a kind of medicinal herb which has strong antioxidant properties has been traditionally used for treating various ailments including skin inflammatory diseases. To date, the anti-inflammatory efficacy of C. gynandra based cream has not been reported. The aim of the study was to evaluate the anti-inflammatory activities of C. gynandra leaf extract cream using an in vivo arachidonic acid-induced ear edema in the rat model. The expression of genes related to rat ear inflammation was measured to evaluate the topical anti-inflammatory activity of C. gynandra cream. The toxicity effect of C. gynandra cream was determined through a skin irritation test in rats and human cumulative skin irritation assessment. Data collected evidently showed a significantly higher (p<0.05) percentage of recovery rate (70.21±5.14%) in rats treated with C. gynandra cream when compared to the negative control (27.43±4.75%) and basal cream (55.8±4.61%), indicating that C. gynandra cream effectively reduced inflammation symptoms in rat ear edema model study. The expressions of all pro-inflammatory cytokines and acute inflammatory-related genes were significantly down-regulated in C. gynandra cream-treated group than untreated group (negative control). The dermatological safety aspect of C. gynandra cream was confirmed by human cumulative skin irritation assessment with the average cumulative irritation index of 0.046, indicating a non-irritating effect. The overall findings demonstrated that C. gynandra cream has great potential to be applied for treating skin-related inflammatory diseases. © 2024 The Authors. Published by Rynnye Lyan Resources.